The diversification of charities: from religion-oriented to for-profit-oriented fundraising - Saunders, Stephen Graham (International journal of nonprofit and voluntary sector marketing, 2013)
Charities are increasingly relying on more complex and diversified fundraising structures to raise funds and attract benefactors. In adopting a historic perspective, this research identified five emergent fundraising structures, namely religion‐oriented, business‐oriented, marketing‐oriented, consumer‐oriented, and for‐profit‐oriented. The analysis critically evaluates the role that institutions and resources have played in each funding structure and draws conclusions concerning the management of charitable fundraising in a world where charitable fundraising, consumerism, and social media networking are increasingly entwined with the for‐profit motive. Copyright © 2012 John Wiley & Sons, Ltd.